PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR PUSAT PT. CITRA BUANA PRAKARSA - Shinta Wahyu Hati; Indira Brahmana (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: The purpose of this study was to determine the effect of direct com- pensation variable and indirect compensation variable on motivation variable, to determine the effect of direct compensation variable and indirect compen- sation variable on employee performance variable, and to determine the effect of direct compensation and indirect compensation variable on employee per- formance variable with motivation as intervening variable This kind of re- search is explanatory research with quantitative approach by using question- naire. Research sample are 55 employee of PT. Citra Buana Prakarsa. This re- search use descriptive analysis method, path analysis, partially and simul- taneity trial. Statistical calculations show that direct compensation  signify- cantly contributing to work motivation with value 0.347, and indirect compen- sation significantly contributing the work motivation with value 0.379. Direct compensation significantly contributing to employee performance with value0.590. Indirect compensation significantly contributing to employee perfor- mance with value 0.529. The results of this study are direct compensation, indi- rect compensation, and work motivation have a significant influence on em- ployyee performance. Keyword : Compensation, Employee Performance, Motivation